Răspuns:
Explicație pas cu pas:
E(x)= [tex]\frac{x^{2} }{x^{2} +1}[/tex]
F(x)= [tex]\frac{1}{x^{2} +1}[/tex]
E(-2)= [tex]\frac{\frac{-1}{2} ^{2} }{\frac{-1}{2}^{2} +1 }[/tex]=[tex]\frac{\frac{1}{4} }{\frac{1}{4} +1}[/tex]=[tex]\frac{\frac{1}{4} }{\frac{5}{4} }[/tex]=[tex]\frac{1}{4} *\frac{4}{5}[/tex]=[tex]\frac{1}{5}[/tex](1)
E(-[tex]\frac{1}{2}[/tex])=[tex]\frac{5}{4\\}[/tex]
F(-2)=[tex]\frac{1}{(-2)^{2}+1 }[/tex]=[tex]\frac{1}{4+1}[/tex]=[tex]\frac{1}{5}[/tex](2)
Din (1) și (2) => că E(-[tex]\frac{1}{2}[/tex])=F(-2)